DEVELOPING COMIC-BASED STUDENT WORKSHEETS ON POSTER AND SLOGAN WRITING MATERIALS - Ninit Alfianika; Silvia Marni (Universitas Negeri Yogyakarta, 2019)
This study was aimed at producing a valid, practical, and effective comic-based student worksheet for writing slogans and posters on Indonesian language learning. The development research was designed using a 4D model (define, design, develop, disseminate) and limited to the third stage. The subject of the study included experts in content validation, teachers in the practicality test and class VIII students as a trial of product use. The instruments used in data collection in this study were validation questionnaires, observation sheets, and performance tests. The data in the form of questionnaire validation, practicality, activity, and student learning outcomes then were processed quantitatively. The worksheet consists of 8 themes. The results show that the developed comic-based Indonesian worksheet for the material of writing slogans and posters is vaild, practical and effective to facilitate the development of activities and student learning achievement. This worksheet is able to be used as teaching materials to improve the quality of the process and results of learning Indonesian.PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS KOMIK PADA MATERI MENULIS POSTER DAN SLOGAN Tujuan penelitian ini adalah untuk menghasilkan Lembar Kerja Siswa (LKS) berbasis komik yang valid, praktis, dan efektif untuk materi menulis slogan dan poster pada pembelajaran Bahasa Indonesia. Penelitian pengembangan didesain dengan menggunakan model 4D (define, design, develop, disseminate) dan dibatasi sampai pada tahap ketiga. Subjek penelitian mencakup ahli dalam validasi konten, guru dalam uji praktikabilitas dan siswa kelas VIII sebagai uji coba penggunaan produk. Instrumen yang digunakan dalam pengumpulan data dalam penelitian ini adalah angket validasi, lembar observasi, dan tes unjuk kerja. Data penelitian berupa skor angket validasi, praktikalitas, aktivitas, dan hasil belajar siswa dan diolah secara kuantitatif. LKS yang dihasilkan terdiri dari 8 tema Berdasarkan analisis data dapat disimpulkan bahwa LKS bahasa Indonesia berbasis komik untuk materi manulis slogan dan poster yang dikembangkan sangat valid sangat praktis dan sangat efektif untuk memfasilitasi pengembangan aktivtas dan prestasi belajar siswa. LKS yang dihasilkan dapat digunakan sebagai bahan ajar untuk meningkatkan kualitas proses dan hasil pembelajaran bahasa Indonesia.